The Role of Leader Member Exchange (LMX), Organization Citizenship Behavior (OCB) on Organizational Commitment and Performance: An Empirical Study on Indonesian SMEs - Teguh Iman Santoso; Hazriyanto Hazriyanto; Moch Aminudin Hadi; Ratna Komala Putri; Siti Aminah (Universitas Negeri Makassar, 2022)
The purpose of this research is to analyze the relationship between leader member exchange (LMX) on organizational citizenship behavior (OCB), organizational commitment on organizational citizenship behavior (OCB), leader member exchange (LMX) on performance, organizational commitment on performance and OCB on performance. This study used a quantitative method and the respondents to this study were 370 SMEs owners in Jabotabek who were selected using a simple random sampling method. Research data was obtained by distributing questionnaires online through social media. The questionnaire was designed using a Likert scale from 1 to 7. Data analysis used a structural equation model (SEM) with the data processing tool SmartPLS 3.0 software. The stages of testing the data are validity, reliability and hypothesis testing. The independent and dependent variables in this study are LMX, OCB, Organizational Commitment and performance. The results of this study indicate that leader member exchange (LMX) has a positive and significant effect on organizational citizenship behavior (OCB), organizational commitment has a positive and significant effect on organizational citizenship behavior (OCB), Leader member exchange (LMX) has a positive and significant effect on performance, Organizational commitment has a positive and significant effect on performance, OCB has a positive and significant effect on performance.